The Time for Doing is Not the Time for Change: Effects of General Action and Inaction Goals on Attitude Retrieval and Attitude Change - Albarracín, Dolores (2011)
Implicit in many informal and formal principles of psychological change is the understudied assumption that change requires either an active approach or an inactive approach. This issue was systematically investigated by comparing the effects of general action goals and general inaction goals on attitude change. As prior attitudes facilitate preparation for an upcoming persuasive message, general action goals were hypothesized to facilitate conscious retrieval of prior attitudes and therefore hinder attitude change to a greater extent than general inaction goals. Experiment 1 demonstrated that action primes (e.g., “go,” “energy”) yielded faster attitude report than inaction primes (e.g., “rest,” “still”) among participants who were forewarned of an upcoming persuasive message. Experiment 2 showed that the faster attitude report identified in Experiment 1 was localized on attitudes towards a message topic participants were prepared to receive. Experiments 3, 4, and 5 showed that, compared to inaction primes, action primes produced less attitude change and less argument scrutiny in response to a counterattitudinal message on a previously forewarned topic. Experiment 6 confirmed that the effects of the primes on attitude change were due to differential attitude retrieval. That is, when attitude expression was induced immediately after the primes, action and inaction goals produced similar amounts of attitude change. In contrast, when no attitude expression was induced after the prime, action goals produced less attitude change than inaction goals. Finally, Experiment 7 validated the assumption that these goal effects can be reduced or reversed when the goals have already been satisfied by an intervening task.